Why are we not walking? Introspective reconstructions of the north–south global climate change conundrums - Muchaku, Shadreck; Zhou, Leocadia (Frontiers in Human Dynamics, 2025)
Effective climate change adaptation and mitigation (CCAM) require strong cooperation between countries in the global north (GN) and global south (GS). However accomplishing this is often constrained by power asymmetries and conflicting interests. This disjunction and lack of selfless willingness to assimilate practically implementable interventions are a challenge that needs to be collectively addressed. This paper draws on a systematic review of 35 peer-reviewed studies to demonstrate how global guidelines frequently prioritize GN interests, impose disproportionate costs on the GS, and overlook local contexts and indigenous knowledge. Key barriers include the GN’s reluctance to acknowledge historical responsibility for greenhouse gas emissions, short-term energy security concerns that drive a return to fossil fuels, the “classification conundrum” surrounding emerging economies such as China and corruption and conditional aid that undermine climate finance. Despite these challenges, the study identifies actionable pathways. A just energy transition that links renewable energy expansion with social equity can align global mitigation efforts with development needs. Incorporating nature-based and locally adapted solutions fosters legitimacy and community ownership, while South–South cooperation provides complementary avenues for sharing technologies and indigenous practices. The paper urges international organizations to reform climate finance by favoring grants over debt-inducing loans and to enhance inclusive decision-making to combat “carbon colonialism” and greenwashing. By synthesizing these insights, the study offers an evidence-based framework for equitable North–South collaboration, presenting practical strategies to bridge divides and accelerate progress toward global sustainability goals.